Analisis Gerakan Literasi Baca Tulis di Kelas II SDN-12 Palangka Kota Palangkaraya - Wulandari, Yeny; Mardiana, Dina (Jurnal Pendidikan Dasar dan Menengah, 2024)
The aim of this research was to analyze the implementation of the School Literacy Movement (GLS) Program at SDN-12 Palangka, as well as to find out the supporting and inhibiting factors during the implementation of the GLS Program. This research opted qualitative ethnopedagogical design with a descriptive method. Data collection was carried out through observation, interview, and documentation techniques. The subjects were the school principal, teacher of the second graders, students of the second graders, and parents of those students. To analyse the data, researchers used procedures from Miles and Huberman which included data reduction, data presentation, and drawing conclusions and verification. The results showed that the implementation of GLS program for the second-grade students of SDN-12 Palangka were varied based on the adapting stage, developing stage and learning stage. In the adapting stage, the 15-minute reading activities provided a reading corner in the classroom, a cultural activity of reading and writing literacy, and a public involvement for students. In the developing stage, the activity facilitated a guided reading activity and reading togetherness for students. Then, in the learning stage it organized several literacy-based classes for learning, carried out reading and writing literacy evaluations, and built a school literacy team. The benefits of the GLS program conveyed supporting factors such as facilitating a reading corner in the classroom, learning posters, a cooperation between all school components and parental involvement. However, the program also has inhibiting factors such as the lack of varied reading books in the school library, and the negative reading habit of students where they are not familiar with reading activity.